PERUBAHAN FISIKO-KIMIAWI, MIKROBIOLOGI DAN HISTAMIN BAKASANG IKAN CAKALANG SELAMA FERMENTASI DAN PENYIMPANAN [Physico-Chemical, Microbiological, and Histamine Changes in Skipjack Bakasang During Fermentation and Storage] - Sri Purwaningsih; Joko Santoso; Rahmatia Garwan (Jurnal Teknologi dan Industri Pangan, 2013)
Bakasang is a salted fermentation product made from viscera of skipjack (Katsuwonus pelamis, Lin) or tuna (Thunnus sp) which tastes sour and is usually used as a complementary dish for local people in Ternate, North Maluku, Indonesia. The research aimed to study the changes in protein and histamine levels of bakasang made from skipjack viscera during fermentation and during storage at room temperature. The experiment consisted of preparation and characterization of raw materials, fermentation for 0, 2, 4, 6, and 8 days, and storage of the resulted product at room temperature for 0, 30, 60, and 90 days. The best bakasang obtained from this experiment was compared with a commercial bakasang produced by local people in Ternate. Fermentation time gave significant effects on the moisture, protein, histamine, and total microbes but did not affect pH and Salmonella count. Bakasang with the best characteristics was obtained after 4 days of fermentation. The product  contained protein, pH, histamine, and  log total microbe of 50.87% (db), 5.78, 24.56 ppm, 4.86 log CFU/g, respectively. During room temperature storage, the level of moisture, protein, and histamine as well as pH and total bacteria changed significantly. Bakasang stored for 30 days had the best characteristics. It contained protein, histamine, and log total microbes of 46.98% (db), 28.97 ppm, and 4.66 logCFU/g, respectively. The characteristics of bakasang in this study were better than commercial bakasang which had protein, histamine, and log microbes of 44.48% (db), 303.37 ppm and 7.36 log CFU/g, respectively.